The Path of Price Changes in Vertical Integration - Quirmbach, Herman C. (Journal of Political Economy, 1986)
The paper examines the path of final good price changes when a monopoly supplier of an intermediate good vertically integrates into a competitive, constant returns final good industry. I show that the price rises while the monopolist is taking over the downstream industry and then falls after downstream monopolization is complete. The relationship of these results to the existing literature on full forward integration is established.